Effects of late aerobic exercise on cardiac remodeling of rats with small myocardial infarction. (25th November 2020) - Souza, L.M; Okoshi, M.P; Gomes, M.J; Rodrigues, E.A; Pontes, T.H.D; Damatto, F.C; Oliveira, L.R.S; Lima, A.R.R; Gatto, M; Borim, P.A; Zornoff, L.A.M; Okoshi, K; et al.
Abstract: Background: Physical exercise has been highlighted as an important non-pharmacological therapy for prevention and treatment of several cardiovascular diseases. However, its effects on hearts with minor cardiac remodeling are not clear. Purpose: To evaluate the influence of aerobic physical exercise on functional capacity, cardiac structure, left ventricular (LV) function, and gene expression of NADPH oxidase subunits in rats with small-sized myocardial infarction (MI). Methods: Three months after MI induction, Wistar rats were divided into three groups: Sham; sedentary MI (MI-SED); and aerobic exercised MI (MI-EA). Rats exercised three times a week for 12 weeks on a treadmill. Echocardiogram was performed before and after experimental period. Infarction size and cardiomyocyte diameters were evaluated by histology. Gene expression was assessed by RT-PCR. Results: Only rats with MI size lower than 30% of LV total area were included in the study. Functional capacity was higher in MI-AE than the other groups. Infarction size did not differ between groups. Infarcted rats had increased LV diastolic and systolic diameter, left atrial diameter, and LV mass, with systolic dysfunction. LV diastolic posterior wall thickness was higher in MI-AE than Sham, and relative wall thickness was lower in MI-SED than MI-AE and Sham groups. Cardiomyocyte diameter was smaller in infarcted groups than Sham. Myocardial gene expression of the NADPH oxidase subunits NOX2, NOX4, p22phox, and p47phox did not differ between groups. Conclusion: Small-sized myocardial infarction changes cardiac structures and left ventricular systolic function. Late aerobic physical exercise improves functional capacity and cardiac remodeling by preserving left ventricular geometry. NADPH oxidase subunits gene expression is not involved in cardiac remodeling or modulated by aerobic exercise in rats with small myocardial infarction. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): CNPq; CAPES